Letters of rejection: The unwelcome news - Bosch Abarca, Elena; Giménez Moreno, Rosa (The ESPecialist, 2008)
The study examines the politeness phenomenon of ‘unwelcome news letters’. We try to formulate the ways in which writers express their needs to repair the possible damage caused to an applicant for having his/her job application rejected. Drawing on Brown and Levinson’s work (1978; 1987), thirty letters of rejection are examined – sixteen of them being analysed in detail – in terms of the addressors’ concerns to avoid face-threatening acts.